Shimming effect on the mechanical behaviors of composite assembly structures of aircraft. (March 2019) - Gao, Guoqiang; An, Luling; Zhang, Wei; Ge, Ende; Yue, Xuande; Yun, Yishen; Han, Ning
The mechanical behaviors of composite assembly structures of aircraft might change due to filling the fit-up gap between two components with liquid shim or laminated shim. In order to investigate the change qualitatively and quantitatively, a kind of implicit nonlinear finite element models are developed, and mixed failure criteria considering the nonlinear shear relationship between composite matrix and fiber, out-of-plane stresses, and buckling of fiber are incorporated into finite element models. And tensile experimental research is also performed to validate the finite element models. Good agreement between the numerical and experimental results builds confidence that the finite element models are effective in predicting the shimming effect. And it is also observed that the mechanical behaviors of composite assembly structures with different filling present obvious differences.